Concise Synthesis of the Antiplasmodial Isocyanoterpene 7, 20‐Diisocyanoadociane. Issue 39 (27th August 2019) - Karns, Alexander S.; Ellis, Bryan D.; Roosen, Philipp C.; Chahine, Zeinab; Le Roch, Karine G.; Vanderwal, Christopher D.
Abstract: The flagship member of the antiplasmodial isocyanoterpenes, 7, 20‐diisocyanoadociane (DICA), was synthesized from dehydrocryptone in 10 steps, and in 13 steps from commercially available material. Our previous formal synthesis was reengineered, leveraging only productive transformations to deliver DICA in fewer than half the number of steps of our original effort. Important contributions, in addition to the particularly concise strategy, include a solution to the problem of axial nucleophilic methylation of a late‐stage cyclohexanone, and the first selective synthesis and antiplasmodial evaluation of the DICA stereoisomer with both isonitriles equatorial. Abstract : The flagship antiplasmodial isocyanoterpene, 7, 20‐diisocyanoadociane (DICA), was constructed in ten steps from simple starting materials. An additional important contribution is a solution to the problem of axial nucleophilic methylation of a late‐stage cyclohexanone, and the first selective synthesis and antiplasmodial evaluation of the DICA stereoisomer with both isonitriles equatorial.